Creating polar antivortex in PbTiO3/SrTiO3 superlattice - Adeel Y. Abid (Nature Portfolio, 2021)
While the role of PbTiO3 in PbTiO3/SrTiO3 superlattices has been widely studied, little attention is paid to possible polar topologies in SrTiO3. Here, the authors create atomic-scale vortex–antivortex pairs in the superlattices, expanding the understanding of topological structures.